Pengaruh Profitabilitas dan Ukuran Perusahaan Terhadap Harga Saham: Studi Kasus pada Perusahaan Sub-Sektor Perbankan yang Terdaftar di Bursa Efek Indonesia Periode 2019-2023 - Wanda Aulia Rachman; Vita Citra Mulyandini (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
This study aims to determine and analyze the effect of profitability and firm size on stock prices of banking sub-sector companies listed on the Indonesia Stock Exchange for the 2019-2023 period. The background of this research is the fluctuation of stock prices influenced by internal factors such as profitability and firm size, but previous research results still show inconsistencies. The research method used is quantitative with a case study approach. The sample in this study was selected using purposive sampling and consisted of 29 banking companies with five years of observation, resulting in a total sample of 145 that met the sampling criteria. The data used are secondary data in the form of annual financial reports analyzed using multiple linear regression with classical assumption tests. The results show that profitability has a positive and significant effect on stock prices, and firm size also has a positive and significant effect on stock prices both partially and simultaneously. These findings support signaling theory, which explains that financial information can be used as an indicator of a company’s performance. This research is expected to serve as a consideration for investors in making investment decisions and for companies to maintain sound financial performance.